Research Progress on the Mechanism of Sepsis Induced Myocardial Injury - Bi CF; Liu J; Yang LS; Zhang JF (Dove Medical Press, 2022)
Cheng-Fei Bi,1- 3,* Jia Liu,2,4,* Li-Shan Yang,1 Jun-Fei Zhang1- 3 1Department of Emergency Medical, General Hospital of Ningxia Medical University, Yinchuan, People's Republic of China; 2School of Clinical Medicine, Ningxia Medical University, Yinchuan, People's Republic of China; 3Key Laboratory of Hui Ethnic Medicine Modernization, Ministry of Education, Ningxia Medical University, Yinchuan, People's Republic of China; 4Medical Experimental Center, General Hospital of Ningxia Medical University, Yinchuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Li-Shan Yang; Jun-Fei Zhang, Email nyfyyls@126.com; zhangjunfei007@126.comAbstract: Sepsis is an abnormal condition with multiple organ dysfunctions caused by the uncontrolled infection response and one of the major diseases that seriously hang over global human health. Besides, sepsis is characterized by high morbidity and mortality, especially in intensive care unit (ICU). Among the numerous subsequent organ injuries of sepsis, myocardial injury is one of the most common complications and the main cause of death in septic patients. To better manage septic inpatients, it is necessary to understand the specific mechanisms of sepsis induced myocardial injury (SIMI). Therefore, this review will elucidate the pathophysiology of SIMI from the following certain mechanisms: apoptosis, mitochondrial damage, autophagy, excessive inflammatory response, oxidative stress and pyroptosis, and outline current therapeutic strategies and potential approaches in SIMI.Keywords: sepsis induced myocardial injury, mechanism, signaling pathway